Internalisasi Nilai-nilai Spiritual dan Sosial Santri Dalam Shalat Berjamaah (Penelitian di Pondok Pesantren La Tansa Islamic Boarding School Parakansantri, Lebakgedong, Lebak-Banten) - M. Syara Nurhakim (Almarhalah | Jurnal Pendidikan Islam, 2021)
AbstractThis research is motivated by the lack of application of spiritual and social values which are considered important in the implementation of congregational prayers in order to achieve the goal of perfect worship, both physically and mentally. The purpose of this study is to determine the meaning of the spiritual and social values of students in congregational prayers at the La Tansa Islamic Boarding School. To find out the process of applying the spiritual and social values of students in congregational prayers, as well as their implications for the lives of students at the La Tansa Islamic Boarding School. The research method used is a qualitative research method. The data collection tools used observational analysis, interviews, and documentation studies. The results of this study indicate that spiritual values are values contained in the human soul, which in the human soul has a spirit. The essence of spiritual value is the spirit. Everyone must have a spirit and that spirit is in their own soul. The only one who knows about the spirit is Allah while the creatures do not. While social values are values held by society, regarding what is considered good and what is considered bad by society.Keywords: Social Values, Spiritual Values, Islamic Boarding School